Rayén Lafkén: emancipación y resistencia económica en una cooperativa de mujeres mapuche - Daniela Beatriz Miranda Prado (Les Cahiers ALHIM)
This article addresses the resistance process of a group of women belonging to the Mapuche Lafkenche people from a particular sphere, the economic sphere. The group Rayén Lafkén (flower of the sea) is a work cooperative that produces a snack made of cochayuyo (edible seaweed), composed exclusively of women who seek to develop a work centre in the commune of Tirúa, a backward area with high rates of poverty and territorial isolation, and classified by the State of Chile as a "conflict zone", as a result of the historical confrontation of the Mapuche nation with the State of Chile for the recovery of their ancestral lands. The article analyses the history of the cooperative from the approach of the feminist economy (FE) and the social and solidarity economy (SSE) - within which cooperativism is inscribed-describing how these women carry out tasks that seek to reclaim an economic activity that places good living at the center, practicing an ancestral trade in whose production chain the whole family participates and expanding the possibilities of labour insertion of their children, but especially of their daughters, whose only possible way of economic insertion is usually domestic service.